PATIENTS` SATISFACTION WITH LABORATORY SERVICES AT SELECTED MEDICAL-DIAGNOSTIC LABORATORIES IN VARNA. - Emilia Georgieva; Gabriela Tsankova; Violina Kaludova; Neli Ermenlieva (Peytchinski Publishing, 2014)
Aim: To establish the degree of patient satisfaction as factors of quality diagnostic laboratory activity. Materials and methods: Patients` satisfaction with laboratory service was studied by means of an anonymous inquiry of 150 patients from Varna during the February - April 2013. Results and Discussion: The maximum patient satisfaction of laboratory studies indicates a high level of the diagnostic laboratories. The quality of the medical service and professionalism of the staff is the main reason for the patients' preferences. These estimates have an increasing importance for the future of diagnostic laboratories in a developing market of an economy and health system based on the patient choice. Conclusion: Quality of the medical service and professionalism of the staff is the main motive for the preferences of patients, followed by good attitude and personal attention. The overall degree of patients' satisfaction with the laboratory services was high.